2021
DOI: 10.3390/pathogens10030256
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Crisis Creates Opportunity towards Global Monitoring & Surveillance

Abstract: The spectrum of emerging new diseases as well as re-emerging old diseases is broadening as infectious agents evolve, adapt, and spread at enormous speeds in response to changing ecosystems. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a recent phenomenon and may take a while to understand its transmission routes from less traveled territories, ranging from fomite exposure routes to wastewater transmission. The critical challenge is how to negotiate with such catastrophic pandemics in high-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 291 publications
0
15
0
Order By: Relevance
“…The joint research center of the European Union (JRC) has shown a correlation between the number of people infected in a sewershed and the viral load in wastewater [ 222 ]. Results also showed that the viral load in the sewage increases before the number of infected persons increases [ 22 , 223 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The joint research center of the European Union (JRC) has shown a correlation between the number of people infected in a sewershed and the viral load in wastewater [ 222 ]. Results also showed that the viral load in the sewage increases before the number of infected persons increases [ 22 , 223 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of a lack of such reliable epidemiological data, wastewater surveillance can still be used in less favored conditions. Nevertheless, wastewater surveillance can be useful in three main categories [ 222 , 223 ]: As an early-warning tool to detect (re-)emergence of the pandemic in a specific sewage catchment area; As a management tool to identify the prevalence and trend of infection, as well as to determine low- or high-risk areas, for example, if surveillance data shows the absence of virus in wastewater, the corresponding community can be considered as of low risk; and As a safety factor in cases where testing of residents shows negative results but the virus is detected in wastewater, then further investigations should be prescribed—it can also be useful to evaluate the safety of tourists’ facilities with a controlled environment, such as cruise ships and other similar facilities.…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) indicates the pivotal importance of mass testing in the find–test–trace–isolate–support strategy to contain COVID-19 transmission ( 1 ). The increase in massive testing capacity coupled with artificial intelligence multidisciplinary data should be used to prevent and combat the negative effects of COVID-19 and strengthen global health public systems to improve COVID-19 response ( 2 ). The National Institute of Health supports a rapid scaling up of SARS-CoV-2-detecting tests in the United States ( 3 ); however, the need for better diagnostic tests with high sensitivity has been considered critical to mitigate and suppress the spread of COVID-19 ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It imposes the development of new strategies for COVID-19 diagnosis; however, despite the colossal demand for novel diagnostic platforms with non-invasive and self-collection samples of COVID-19, the accuracy of salivary SARS-CoV-2 platforms are still not well-elucidated. The pivotal impact on social, health, economic, and educational fields in a global emergency due to COVID-19 makes it more challenging to compare the advantages and limitations in implementing novel potential salivary platforms ( 1 , 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although inhalation of aerosol/droplet and person-to-person contact are the major transmission routes of SARS-CoV-2, current evidence points out that the viral RNA is detected in wastewater, urging the need to better understand wastewater as potential source of epidemiological data and human health risks, which can be applied as an early warning system [16][17][18][19]. SARS-CoV-2 may cause asymptomatic or pauci-symptomatic infections [20][21][22], which could add more limitations to determine the actual degree of SARS-CoV-2 circulation in a community.…”
Section: Introductionmentioning
confidence: 99%